Sub-50 nm optical imaging in ambient air with 10× objective lens enabled by hyper-hemi-microsphere - Guangxing Wu; Yan Zhou; Minghui Hong (Light: Science & Applications, 2023)
The hyper-hemi-microsphere fabricated by FIB milling can resolve ~50 nm feature by only coupling with a 10× objective lens (NA = 0.3) in virtual imaging mode.